Antibiotic resistance genes in pipe wall biofilm under eight disinfection strategies in domestic hot water system: Occurrence, removal and interactions. (October 2021) - Li, Na; Li, Xing; Yang, Yan-Lin; Fan, Xiao-Yan
Abstract: For comprehensive insights into the effects of disinfection strategy on antibiotic resistance genes (ARGs) in pipe wall biofilm to ensure the biosafety of domestic hot water system (DHWS), this study investigated the occurrence, removal and interactions of ARGs, as well as their potential hosts. The shifts in biofilm community composition and microbial functions (level three) were observed under different disinfection strategies. A total of 40 ARG subtypes within seven antibiotic types were predicted. The total gene counts ranged from 6.10 × 10 4 to 2.31 × 10 5, and decreased after the chlorine, chlorine dioxide, silver ions (Ag + ), ultraviolet (UV), and Ag + -UV disinfection. The ARGs in samples under different disinfection strategies were divided into four groups, and the removal and enrichment of the same ARGs in each group were almost consistent. The complex interactions among ARGs were weakened and altered by disinfection (edges decreased from 237 to 178), with yebQ and marC as the hub ARGs, but positive correlations were still dominant. Moreover, 36 nonpathogenic bacteria, including high- ( Blastocatella ), mid- ( Ornatilinea ) and low-abundant genera ( Bdellovibrio ), as well as 18 potential pathogens ( Vibrio and Bacillus ) were identified as the potential hosts harboring ARGs. Overall, this study provides some new insights into the occurrence of ARGs and their fate under eight disinfection strategies, which is of great significance for a comprehensive understanding and control of ARGs in DHWS. Graphical abstract: Unlabelled Image Highlights: Cl2, ClO2, Ag +, UV and Ag + -UV reduced the total abundance of 40 ARGs. Eight disinfection strategies could remove specific ARGs to varying degrees. Disinfection weakened and altered the complex interactions among ARGs. yebQ and marC became the hub ARGs after disinfection. Some low-abundant genera were also identified as the potential hosts of ARGs.